The nurse facing cervical cancer: a narrative review (Research, Society and Development, 2023)
Cervical cancer is one of the main causes of death among women in Brazil. The study aims to conduct a survey of scientific research on the role of nurses in the promotion and prevention of cervical cancer. The SCIELO databases were used; LILACS Literature and Virtual Health Library. Inclusion criteria were scientific articles published from 2013 to 2023, in Portuguese, available in full, online and free of charge, in which 10 articles were selected after thorough reading. The diagnosis of cervical cancer is carried out through the Pap smear, which detects changes in the cells of the cervix, and by biopsy, which confirms the presence of cancer cells in the cervical tissue. Colposcopy is indicated when the cytopathological examination presents suspicion of malignancy or is not conclusive for the diagnosis of cervical cancer. In this sense, the Pap smear test is essential for the prevention of cervical cancer and can be performed by trained nurses. The nurse together with a multidisciplinary team can make a difference with regard to the active search and reception of women who need health-related information. Investing in training and valuing the nursing team, as well as in public policies for the care of patients with cervical cancer, is crucial to ensure integrated, humanized and quality care. This promotes the improvement of quality of life and prognosis of the disease for women.